German exports: Impact on the selected EU countries - Marek Juráček (Review of Economic Perspectives, 2021)
This research focuses on the impact of German exports on exports of the other selected EU countries. We used the Global VAR approach to build a robust trade model between 23 EU countries, the USA, and China. By stressing this model with different shocks, we were able to observe how exports of the EU countries react to German loss of competitiveness and decline of demand from Germany. Based on our simulation, we could identify countries which i. are Germany's competitors and would benefit from German loss of competitiveness, ii. are tied with German trade so tightly that loss of German competitiveness would negatively affect their exports.
Keywords: F14; F15; F45; 330; International trade; Global VAR; German exports; European Union